1995
DOI: 10.1021/bi00020a031
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the CP47 Protein in Stabilization and Photoactivation of a Functional Water-Oxidizing Complex in the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: Oscillation patterns of the oxygen yield per flash induced by a train of single-turnover flashes were measured as a function of dark incubation and different pre-illumination conditions in several autotrophic mutant strains of Synechocystis sp. PCC 6803 carrying short deletions within the large, lumen-exposed hydrophilic region (loop E) of the chlorophyll a-binding photosystem II protein CP47. A physiological and biochemical characterization of these mutant strains has been presented previously [Eaton-Rye, J. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 54 publications
6
32
0
Order By: Relevance
“…The model also shows a vicinity of CP47 and the external 33 kDa protein which is supported by structural and functional data (Burnap and Sherman 1991; Gleiter et al 1995;Ohta et al 1995).…”
Section: Structure Of Isolated Dimeric Pssupporting
confidence: 73%
“…The model also shows a vicinity of CP47 and the external 33 kDa protein which is supported by structural and functional data (Burnap and Sherman 1991; Gleiter et al 1995;Ohta et al 1995).…”
Section: Structure Of Isolated Dimeric Pssupporting
confidence: 73%
“…Although site directed mutagenesis reveals that several amino acid residues of D1 and D2 are of functional and/or structural relevance in establishing a competent WOC [8–13], other polypeptides cannot be excluded as potential candidates for being essential constituents of the WOC. It was recently shown that the large lumen exposed loop E of the chlorophyll containing 47 kDa protein (CP47) is essential for the dark stability of the WOC [14–16] and the regulation of its chloride demand [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These polypeptides are also important in stabilising the reaction centre core and modify quinone binding. CP47, especially a sequence forming a large hydrophilic loop, is involved in stabilising the WOC [119].…”
Section: Other Core Polypeptidesmentioning
confidence: 99%